2013
DOI: 10.1093/hmg/ddt596
|View full text |Cite
|
Sign up to set email alerts
|

Human iPSC models of neuronal ceroid lipofuscinosis capture distinct effects of TPP1 and CLN3 mutations on the endocytic pathway

Abstract: Neuronal ceroid lipofuscinosis (NCL) comprises ∼13 genetically distinct lysosomal disorders primarily affecting the central nervous system. Here we report successful reprograming of patient fibroblasts into induced pluripotent stem cells (iPSCs) for the two most common NCL subtypes: classic late-infantile NCL, caused by TPP1(CLN2) mutation, and juvenile NCL, caused by CLN3 mutation. CLN2/TPP1- and CLN3-iPSCs displayed overlapping but distinct biochemical and morphological abnormalities within the endosomal-lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(133 citation statements)
references
References 64 publications
5
128
0
Order By: Relevance
“…20). We have also recently reported that human CLN3 ⌬ex7/8/⌬ex7/8 NPCs display normal ER morphology, yet upon differentiation into mature neurons, which causes progression of other NCL-related phenotypes such as accumulation of storage material, the ER was dilated (11). These observations combined with the key observation in this study that neuronal lineage cells bearing the common JNCL mutation in Cln3/CLN3 are more sensitive to the effects of thapsigargin-mediated Ca 2ϩ release, might suggest that despite the lack of overt ER stress, JNCL cells may be more poised to elicit such a response to further stressors.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…20). We have also recently reported that human CLN3 ⌬ex7/8/⌬ex7/8 NPCs display normal ER morphology, yet upon differentiation into mature neurons, which causes progression of other NCL-related phenotypes such as accumulation of storage material, the ER was dilated (11). These observations combined with the key observation in this study that neuronal lineage cells bearing the common JNCL mutation in Cln3/CLN3 are more sensitive to the effects of thapsigargin-mediated Ca 2ϩ release, might suggest that despite the lack of overt ER stress, JNCL cells may be more poised to elicit such a response to further stressors.…”
Section: Discussionmentioning
confidence: 86%
“…Human NPCs were derived and maintained as described previously (11). The control line was derived from GM8330-8 patient fibroblasts.…”
Section: Human Neural Progenitor Cell (Npc) Culturementioning
confidence: 99%
See 3 more Smart Citations